The role of endothelial damage and dyslipidemia in the development of cardiovascular pathology in psoriatic arthritis - Zarema R. Khismatullina; Ksenia M. Koreshkova (State Scientific Center of Dermatovenereology and Cosmetology, 2021)
An increased risk of cardiovascular events has now been identified in patients with psoriatic arthritis. The chronic immune-mediated inflammation underlying psoriatic arthritis (PA) leads to the development of dyslipidemia, atherosclerosis and its complications, in particular, a high risk of cardiovascular complications. For PA, dyslipidemias are most characteristic, manifested by an increased level of low and very low density lipoproteins, triglycerides and total cholesterol, which correlates with the activity of the disease. The literature review studied the pathogenesis of dyslipidemias and vascular wall lesions in psoriatic arthritis, analyzed the literature on cardiovascular complications and mortality among patients with PA, studied the issues of total cardiovascular risk, presented the results of numerous clinical studies that allow PA to be considered a disease associated with increased the risk of cardiovascular complications. Considering the role of proinflammatory cytokines in the pathogenesis of psoriatic arthritis, early detection of endothelial lesions represents the most promising direction in the prevention of cardiovascular diseases, which are the main cause of mortality in this group of patients.